Biodegradable and biocompatible agarose-based double-network composite hydrogels embedded with hydroxyapatite@Angelica dahurica polysaccharide composite for wound hemostasis - Liang, Jialing; Farhan, Mohd Said; Xu, Xinyi; Guo, Shirui; Li, Yong; Jing, Zhanxin (Elsevier Ltd, 2025)
A biodegradable and biocompatible agarose-based double-network composite hydrogel embedded with hydroxyapatite@Angelica dahurica polysaccharide composite was fabricated via the chemical crosslinked network and physical crosslinked network in the presence of hydroxyapatite@Angelica dahurica polysaccharide composite. The chemical crosslinked network was formed by the radical polymerization reaction of lysine acrylamide and methyl acrylyl ethyl sulfobetaine, while the physical crosslinked network formed by the thermal reversibility of agarose. The formation and structure of agarose-based double-network composite hydrogels were analyzed using FT-IR, XPS, and SEM, and exhibited a 3D network structure that contained spherical HAP@Adp composite. The effects of composition on the mechanical properties, swelling, and degradation properties of agarose-based hydrogels were investigated, and it was found that these properties could be regulated by controlling the content of HAP@Adp, agarose, and SBMA. The synthesized agarose-based composite hydrogels resulted in good sensitivity and degradation ability with a maximum tensile strength that reached 70.5 KPa with an elongation at break of 160 %. In vitro hemolysis test and in vitro cytotoxicity test showed that agarose-based composite hydrogels had a low hemolysis rate and were non-toxic to L929 cells, which confirmed that they had good biocompatibility. Hemostatic experiments confirmed that the hydrogel could significantly reduce blood loss and shorten the hemostatic time compared with the control group. In addition, it was also found that the agarosebased hydrogel has certain antioxidant properties. Therefore, the synthesized biocompatible and biodegradable agarose-based double-network composite hydrogel has good mechanical and hemostatic properties, indicating its potential application in the field of wound dressing.